RESTORATIVE JUSTICE PRACTICES IN EDUCATION: A QUANTITATIVE ANALYSIS OF SUSPENSION RATES AT THE MIDDLE SCHOOL LEVEL - Katic, Barbara (2017)
The negative effects of retributive disciplinary measures in school settings are well documented. Exclusionary practices, such as suspensions, position students on the school-to-prison pipeline, perpetuating a cycle of failure. Restorative justice practices in educational settings provide an alternative to the retributive approach to student discipline. In this research study, a middle school in California was examined for its implementation of restorative justice practices. Numerical data pertaining to a five-year suspension history report for the school were utilized for the quantitative analyses, and four individual chi-square goodness of fit tests were conducted. The results demonstrated that the implementation of restorative justice played a significant role in the declining student suspensions across school years. It was found that the introduction of restorative practices to the middle school played a role in creating an inclusive school environment, with student suspensions having been applied to a lower proportion of African American and Hispanic students from pre-implementation of restorative justice to post-implementation. Through the use of a restorative framework, students may learn how to solve problems and repair relationships in school and life events, rather than being placed on the school-to-prison pipeline